The effects of employer-sponsored health insurance premiums on employment and wages: Evidence from US longitudinal data - Nicola Ciccarelli (Review of Economic Analysis (REA), 2020)
We analyze the effect of employer-sponsored health insurance premiums on employment and annual wages in the US using a county-level panel dataset for the period 2005-2010. Using variation in medical malpractice payments and variation in medical malpractice legislation over time and within states as the source of identifying variation in the health insurance premiums, we estimate the causal effects of rising health insurance premiums on employment and annual wages. We find that a 10% increase in premiums reduces employment by 1.1 percentage points, and leads to a statistically insignificant reduction of annual wages. Since US counties are characterized by a varying degree of private health insurance coverage, we also test whether the private health insurance coverage is a moderating variable for the relationship between the health insurance premiums and the labor market outcomes analyzed in this study. We find that rising premiums negatively affect the labor market conditions faced by US workers, especially in areas that are characterized by high private health insurance coverage.
Keywords: I1; I13; J0; J3; 330; Employer-sponsored health insurance premiums; Wages; Employment; Panel data; Instrumental variables